The Design of Fiscal Reform Packages : Insights from a Theoretical Endogenous Growth Model - Hodge, Andrew (IMF Working Papers; Working Paper ;, 2016)
This paper studies the impact on growth, welfare, and government debt of fiscal reform packages in a theoretical model drawing together three key features of the endogenous growth literature: (i) investment in technology (in the form of human capital) offsets diminishing marginal productivity of private capital, allowing for perpetual growth in output per capita; (ii) changes in investment behavior because of cuts to distortionary tax rates impact long-run growth; and (iii) public capital has a role influencing total factor productivity and growth. A quantitative simulation using reasonable parameter values suggests that modest capital and/or labor income tax cuts and public investment increases have significant positive effects on consumer welfare but small effects on per capita income growth, where fiscal costs are offset by reductions in unproductive government spending. Capital income tax cuts and public investment increases continue to boost welfare when offset by consumption tax rises (rather than spending cuts), although the welfare benefits of modest labor income tax cuts are outweighed by the costs of a compensating consumption tax increase.